Modeling and Simulation Research on Power-split Hybrid Electric Vehicle. (December 2016) - Cao, Jianfei; Peng, Jiankun; He, Hongwen
Abstract: In this paper, a simulation model of power-split hybrid electric vehicle is established and a type of energy management strategy based on optimum-fuel-economy curve is proposed as well. The model contains blocks which can simulate the real physical components, so its accuracy is improved. Power performance and fuel economy are tested by simulation experiment at NEDC and HWYCOL cycle. The result shows the model is correct and effective. What's more, it uses the energy management strategy, so that the fuel consumption per 100 km is 4.56 in NEDC cycle and 4.42 in HWYCOL cycle.